Preparation method of solvent-free tank bottom plate repairing agent

Through the combination of solvent-free epoxy resin, functional filler and small molecule amine curing agent, combined with step-by-step curing method, a high cross-linked dense paint film is formed, which solves the problem of environmentally friendly repair and insufficient protection capability in the prior art, and achieves an efficient and environmentally friendly tank bottom repair effect.

CN119859448AActive Publication Date: 2025-04-22CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311359208.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The existing technology cannot effectively take into account environmental protection and tank bottom repair protection. The traditional repair methods are costly, risky and have limited protection capabilities for acid and alkaline media.

Method used

Solvent-free epoxy resin is used as the matrix, and different functional fillers are compounded with small molecule amines as curing agents. The internal curing rate of the resin is improved by step-by-step curing method, forming a high cross-linked dense paint film, which is closely attached to the metal surface, hindering the penetration of corrosive media.

Benefits of technology

It realizes efficient and environmentally friendly tank bottom repair, improves the mechanical and corrosion resistance of the repair agent, extends the service life of the storage tank and reduces operating costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a solvent-free tank bottom plate repairing agent. According to the method, a prepolymerization-mechanical blending combined mode is adopted, a small amount of resin and a curing agent mixed solution are polymerized to form a small amount of net-shaped polymerization structures, then the net-shaped polymerization structures are mixed with functional filler, and the net-shaped polymerization structures are uniformly mixed and cured with resin components during use. The prepared coating is high in polymerization degree and large in product molecular weight, and compared with a traditional anti-corrosion coating, the adhesion effect on a base material is better, the strength is higher, and meanwhile the excellent flexibility and anti-corrosion performance are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical raw materials and chemical product manufacturing, and in particular relates to a solvent-free tank bottom plate repairing agent and a preparation method thereof. Background Art

[0002] Due to the presence of a water layer at the bottom of petrochemical storage tanks, electrochemical corrosion caused by chloride ions, hydrogen sulfide, carbon dioxide, and oxygen, as well as bacterial corrosion caused by sulfate-reducing bacteria, is very likely to occur. This type of corrosion acts on the bottom of the tank for a long time, forming a large number of pitting corrosion at the bottom of the tank. In severe cases, it can also cause perforation of the tank bottom, endangering storage and transportation safety and causing waste of raw materials. After corrosion occurs, traditional repair methods include metal welding, reinforcing steel plates, etc., but these methods require the use of open flames or the use of large areas of carbon steel plates, which has a great impact on production. Epoxy zinc-rich electrostatic coating technology, which is an anti-corrosion and antistatic coating for the inner wall of the tank, is also used for tank bottom repair, but traditional epoxy resin coating materials have limited protection against acidic and alkaline media and cannot achieve long-term and efficient protection. In the early stage, Wang Feng and others used epoxy resin as a binder, phenoxypropylene oxide as a plasticizer, and polyethylene polyamine as a curing agent, and prepared a tank bottom repair agent according to a weight ratio of 100:10:(10-12), and used a one-step curing method to cross-link. The different corrosion areas on the tank bottom were repaired by two coating methods, the patching method and the lamination method. In addition, there is no mature steel tank bottom repair material and technology.

[0003] Therefore, in order to improve the repair efficiency and effectively extend the service life of the storage tank, it is necessary to develop an efficient and corrosion-resistant tank bottom repair agent. According to preliminary research and on-site tank area exchanges, it is considered to use epoxy resin as the matrix, compound different functional fillers, and small molecule amines as curing agents. No dispersants, defoamers and other organic solvents are added to prepare a solvent-free epoxy repair material. Summary of the invention

[0004] The purpose of the present invention is to provide a solvent-free tank bottom repair agent and a preparation method thereof, so as to solve the problem that the prior art cannot take into account both environmental protection and efficient repair and protection of the tank bottom.

[0005] According to a first aspect of the present invention, the present invention provides a method for preparing a solvent-free tank bottom repair agent.

[0006] Specifically, the preparation method of the solvent-free tank bottom repair agent of the present invention comprises the following contents: (1) uniformly dispersing the epoxy resin in an organic solvent to obtain an epoxy resin slurry; (2) adding a small molecule amine to a reactor, while introducing nitrogen protection; turning on mechanical stirring to heat the small molecule amine to a pre-crosslinking reaction temperature; after the temperature stabilizes, slowly dripping the resin slurry obtained in step (1) into the reactor until the color of the reaction solution turns light yellow and the color no longer changes; (3) raising the temperature of the reactor to the reaction temperature, and continuing to slowly dropwise add the epoxy resin slurry obtained in step (1) into the reactor. After the temperature stabilizes, continue the reaction until completion; (4) After the reaction is completed, stop heating, turn off the nitrogen, stop stirring, cool to room temperature, and obtain repair agent component A; (5) Evenly mix the epoxy resin, lubricant, inorganic filler and optional organic filler to obtain repair agent component B.

[0007] Furthermore, in the above technical solution, the organic solvent in step (1) includes one or more of ethanol, methanol, and acetone, preferably acetone. The epoxy resin is a conventional epoxy resin in the art, and can be specifically selected from one or more of epoxy resins E44, E51, 170, E12, E20, and E68.

[0008] Furthermore, in the above technical solution, the small molecule amine in step (2) includes one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, N-aminopiperazine, polyamide, and dimethylimidazole, preferably two or more, and most preferably three or more small molecule amines are used in combination.

[0009] Furthermore, in the above technical solution, the process of slowly dripping the resin slurry into the small molecule amine in step (2) is a conventional operation in the art.

[0010] Furthermore, in the above technical solution, the pre-crosslinking temperature of the small molecule amine in step (2) is 80±10°C. When the color of the reaction solution changes during the reaction, it means that new substances are generated, and the addition of the resin slurry should be stopped at this time. During the pre-crosslinking reaction, the mass ratio of the amount of the resin slurry added in terms of epoxy groups to the small molecule amine is 1:10-1:5.

[0011] Furthermore, in the above technical solution, the reaction temperature in step (3) is 100±10°C, and the reaction time is 3.5±1 h. During the reaction, the mass ratio of the total amount of the resin slurry added in terms of epoxy groups to the small molecule amine is 1:10-8:10.

[0012] Further, in the above technical solution, the epoxy resin is used as a repair agent matrix to provide a certain strength and toughness for the repair agent. The lubricant is selected from one or more of alkane oil and dimethyl silicone oil (AR). The alkane oil can be selected from one or more of C6, C10, and C12. The alkane oil acts as a lubricant, which can improve the compatibility of the filler and the resin and make it more evenly dispersed. The inorganic filler includes one or more of ferrosilicon powder, carbon black, calcium carbonate (AR), silicon dioxide (AR), and titanium dioxide (AR). Ferrosilicon powder can be selected from one or more of 75#, 70#, 72#, 65#, and 60#. Carbon black can be selected from one or more of C311, N220, N330, and N550. The inorganic filler is used to fill the gaps between the resins, give the repair agent a certain rigidity and strength, and improve the adhesion with the substrate. Among them, the inorganic filler is preferably used in a compound ratio of two or more thereof. The organic filler can be organic bentonite (AR). Organic fillers have an anti-settling effect and can also improve the anti-corrosion performance of the system.

[0013] Furthermore, the epoxy resin used in step (5) is selected from one or more of epoxy E44, E51, 170, E12, E20, and E68, preferably epoxy E44. The epoxy resin used in step (5) and step (1) is preferably of the same brand. The ratio of epoxy resin, lubricant, inorganic filler and optional organic filler is 100:1.6-1.7:141.6-233.9:5-10. When the repair agent of the present invention is used, the mixing ratio of repair agent component A and repair agent component B is generally 3.1:1-6.5:1.

[0014] Based on research, the applicant found that epoxy resin is widely used in functional protective coatings on the surface of storage tanks, but there is currently no good solution to the problem of corrosion repair on the bottom of storage tanks. Currently, most methods are to replace the bottom plate or to patch the reinforcement plate. This method is costly and causes a lot of resource waste. In addition, the replacement process requires hot work, which is very dangerous. Drawing on the experience of external corrosion protection of storage tanks, it is considered that solvent-free metal repair materials can be applied to the damaged area of ​​the tank bottom. After the material is cured, a high-strength, high-hardness paint film is formed, which can replace the metal steel plate to continue to serve. This method is easy to operate and saves energy, and the solvent-free system is also more environmentally friendly.

[0015] Previous experiments have found that directly blending epoxy resin with curing agent will lead to incomplete cross-linking reaction between resin molecules, which will lead to decreased adhesion of the paint film to metal and its own rigidity and flexibility, and the corrosive medium will pass through the paint film to further corrode the substrate. Therefore, the present invention develops a step-by-step curing method to improve the internal curing rate of the resin, so that it forms a highly cross-linked dense paint film, which is tightly attached to the metal surface, provides rigid support, and hinders the inward transmission of corrosive media, thereby extending the service life of the storage tank and reducing operating costs.

[0016] In the present invention, it is preferred to use a plurality of small molecule amine curing agents in combination in the selection of curing agents, because compared with polyamide, piperazine, and imidazole curing agents, small molecule curing agents have shorter molecular chains, good molecular flexibility, less steric hindrance during the curing reaction with the resin, and higher flexibility. The use of a plurality of small molecule amine curing agents in combination can provide a more accurate molar amount of active amines, and the synergistic effect between the molecules can promote the full cross-linking of the resin molecules and the curing agent.

[0017] Adding functional pigments and fillers such as carbon black, ferrosilicon powder, calcium carbonate, organic bentonite, silica, titanium dioxide, etc. to the paint film system can fill the tiny gaps in the resin and prevent corrosive substances from passing through the paint film and corroding the substrate. At the same time, ferrosilicon powder and the like have a certain affinity to the substrate and help the adhesion of the paint film.

[0018] In summary, the epoxy resin and the curing agent can be pre-cured by a pre-polymerization method, and functional pigments and fillers can be added to the obtained slurry to produce a metallic repair material with high adhesion, heavy corrosion resistance, high strength and high modulus.

[0019] Compared with the traditional method, the coating prepared by this method innovatively adopts a step-by-step polymerization method, firstly cross-linking and curing the curing agent with a small amount of resin, and then adding the remaining resin to completely cure it. This method greatly improves the resin curing rate in the paint film, and obtains a paint film coating with high corrosion resistance and high adhesion. The addition of fillers has a certain beneficial effect on the rigidity, repair and corrosion resistance of the paint film, and the solvent-free property is more in line with the concept of green environmental protection.

[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. By adopting a step-by-step polymerization method for the resin, the contact density between the resin and the curing agent molecules is controlled. In the prepolymerization stage, a small amount of resin molecules are bonded with the curing agent to form a small cross-linked network. When the A and B components are mixed, the resin molecules react with the remaining active amines to connect each small cross-linked network into a whole, greatly improving the degree of polymerization between the resin and the curing agent, making them cross-linked to form a uniform and dense network structure, improving the cross-linking density of the repair agent, and thus improving its overall mechanical properties, with both high strength and high flexibility while resisting the penetration of corrosive media, so that it has a certain corrosion resistance. In the one-step cross-linking polymerization, a large amount of resin and curing agent are in contact at the same time, producing a large number of small cross-linked networks, which are poor in density compared to the step-by-step cross-linking, and thus lead to poor mechanical strength and corrosion resistance.

[0021] 2. When preparing the repair agent, a combination of prepolymerization and mechanical blending is used. First, a small amount of resin and curing agent mixed liquid is polymerized to form a small amount of mesh polymer structure, which is then mixed with functional fillers and evenly cured with the resin components during use. The coating prepared by this method has a high degree of polymerization and a large product molecular weight. Compared with traditional anti-corrosion coatings, it has better adhesion to the substrate, higher strength and excellent flexibility. When used for tank bottom repair, it can cope with large pressure changes in the tank; it has a long service life and does not require repeated painting, and is suitable for a variety of working conditions. At the same time, the system does not add any organic solvents, and there is no VOC volatilization during use, which is environmentally friendly and more environmentally friendly. A highly corrosion-resistant resin is selected as the repair agent matrix to improve the flexibility and mechanical strength of the repair agent while taking into account the anti-corrosion performance.

[0022] 3. In the repair agent provided by the present invention, various functional pigments and fillers such as ferrosilicon powder, carbon black, and alkane oil are added to the coating to fill the resin gaps, improve the adhesion of the repair agent to the metal substrate, and prevent the corrosion medium from penetrating into the interior. The resin, curing agent, and filler promote each other to form a unified whole, which gives the coating certain anti-corrosion and aging resistance on the basis of ensuring the adhesion of the coating. At the same time, ferrosilicon powder and the like have a certain affinity to the substrate, which has a certain beneficial effect on improving the adhesion between the repair agent and the substrate.

[0023] 4. The repair agent system prepared by the method of the present invention is a solvent-free system. No organic solvent is added during use or coating. The small amount of diluent added during the reaction is dissipated and volatilized in the reaction and then recycled, which is harmless to the environment and more environmentally friendly. DETAILED DESCRIPTION

[0024] The present invention will be described in more detail below with reference to specific embodiments.

[0025] Adhesion test: Test the coating adhesion according to the requirements of GB / T 5210-2006 "Adhesion test of paint and varnish by pull-off method".

[0026] Pencil hardness determination: Test according to standard GB / T 6379-2006 "Determination of paint film hardness by pencil method for paints and varnishes". Spray one layer (25±5 μm) on a tinplate with a size of 120 mm×50 mm×0.3 mm. After curing for 7 days, push the pencil hardness tester on the paint film to compare the scratches on the paint film surface when a pencil with a specified hardness is pushed across the paint film surface. The hardness of the coating is expressed by the hardness of the hardest pencil with no defects on the paint film.

[0027] Bending resistance test: Tested according to the standard GB / T 6742-2007 "Bending test for paints and varnishes (cylindrical shaft)". Spray one layer (25±5 μm) on a tinplate with a size of 120 mm×50 mm×0.3 mm, and after curing for 48 hours, perform a bending test on a type II bending tester to observe whether there are cracks, peeling, etc. The maximum shaft diameter (mm) that causes cracking or peeling of the coating is used to indicate the bending resistance of the coating.

[0028] Impact resistance test: Tested according to the standard GB / T 1732-1993 "Determination of impact resistance of paint film". Spray a layer (25±5 μm) on a tinplate with a size of 120 mm×50 mm×0.3 mm. After curing for 48 hours, place the test plate on an impact tester and let a heavy hammer fall freely from a certain height to observe whether there are cracks and other defects. The maximum height (cm) at which a heavy hammer of a specified mass falls on the test plate without causing damage to the paint film is used to indicate the impact resistance of the coating.

[0029] Water resistance test: Test according to GB 1733-1993 "Determination of water resistance of paint film". Spray a layer (25±5 μm) on a tinplate with a size of 120 mm × 50 mm × 0.3 mm and cure for 7 days. Before testing, seal the edges with a 1:1 mixture of paraffin and rosin, then place the test plate in distilled water and soak for at least 48 hours. After reaching the end of the soaking period, thoroughly clean the test plate with distilled water and check the changes in the test plate coating.

[0030] Acid and alkali resistance test: Test according to standard GB 9274-1988 "Determination of resistance of paints and varnishes to liquid media". On a steel plate with a size of 150 mm × 70 mm × 0.5 mm, apply one coat of primer and two coats of topcoat (90 ± 10 μm), paint the front and back of the test plate, and maintain for 7 days. Before the test, seal the edges with a 1:1 mixture of paraffin and rosin, and then place the test plate in a prepared mass fraction of 5% sulfuric acid and 5% sodium hydroxide solution, soak for at least 168 hours. After reaching the end of the soaking period, thoroughly clean the test plate with distilled water, check the changes in the test plate coating, and record the time when the changes occur.

[0031] The resins, curing agents, lubricants and solid fillers used in the examples and comparative examples are all commercially available products. Example 1

[0032] Take 2g of diethylenetriamine, 4.6g of triethylenetetramine, and 4.5g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 10g of epoxy resin E44 and disperse it in 10g of acetone, then place it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 90°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 40min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 110°C. Continue the reaction for 4.5h and then discharge the material to obtain the repair agent component A.

[0033] 93 g of epoxy resin E44, 1.5 g of alkane oil (C12), 199.5 g of ferrosilicon powder (75#), 3.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0034] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties. Example 2

[0035] Take 2g of diethylenetriamine, 6.6g of triethylenetetramine, and 2.5g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 10g of epoxy resin E44 and disperse it in 10g of acetone, then place it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 70°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 45min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 90°C. Continue the reaction for 2.5h and then discharge the material to obtain the repair agent component A.

[0036] 93 g of epoxy resin E44, 1.5 g of alkane oil (C10), 199.5 g of ferrosilicon powder (75#), 3.3 g of carbon black (C311), 6.5 g of organic bentonite (AR), etc. were mixed evenly to obtain repair agent component B.

[0037] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties. Example 3

[0038] Take 7.6g of diethylenetriamine and 3.5g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 10g of epoxy resin E44 and disperse it in 10g of acetone, then put it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 90°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 40min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 110°C. Continue the reaction for 4.5h and then discharge the material to obtain the repair agent component A.

[0039] 93 g of epoxy resin E44, 1.5 g of alkane oil (C12), 199.5 g of ferrosilicon powder (75#), 3.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0040] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties. Example 4

[0041] Take 3.6g of diethylenetriamine, 2g of triethylenetetramine, and 5.5g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 10g of epoxy resin E44 and disperse it in 20g of acetone, then place it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 80°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 50min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 90°C. Continue the reaction for 3.5h and then discharge the material to obtain the repair agent component A.

[0042] 93 g of epoxy resin E44, 1.5 g of alkane oil (C12), 127.5 g of ferrosilicon powder (70#), 3.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0043] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties. Example 5

[0044] Take 2.1g of diethylenetriamine, 2g of triethylenetetramine, and 7g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 15g of epoxy resin E44 and disperse it in 10g of acetone, then place it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 90°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 55min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 100°C. Continue the reaction for 4.5h and then discharge the material to obtain the repair agent component A.

[0045] 88 g of epoxy resin E44, 1.5 g of alkane oil (C12), 199.5 g of ferrosilicon powder (75#), 6.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0046] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties. Example 6

[0047] Take 11.1g of triethylenetetramine and add it to the reactor, pass nitrogen protection to prevent small molecular amines from absorbing water and fuming. Take 10g of epoxy resin E44 and disperse it in 10g of acetone, then put it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 90°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 40min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 110°C. Continue the reaction for 4.5h and then discharge the material to obtain the repair agent component A.

[0048] 93 g of epoxy resin E44, 1.5 g of alkane oil (C12), 199.5 g of ferrosilicon powder (75#), 3.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0049] The repair agent component A and the repair agent component B were mixed evenly in a ratio of 3.5:1, aged for about 5 minutes, and then scraped to form a film. The sample was then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test its physical and anti-corrosion properties.

[0050] Comparative Example 1 Take 103g of epoxy resin E44, mix it evenly with 2g of diethylenetriamine, 4.6g of triethylenetetramine, 4.5g of tetraethylenepentamine, 1.5g of alkane oil (C12), 199.5g of ferrosilicon powder (75#), 3.3g of carbon black (C311), etc., mature it for about 5 minutes, and apply it to form a film.

[0051] The samples were then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test their physical and anti-corrosion properties.

[0052] Comparative Example 2 Take 2g of diethylenetriamine, 4.6g of triethylenetetramine, and 4.5g of tetraethylenepentamine and add them to the reactor. Pass nitrogen to protect and prevent small molecular amines from absorbing water and fuming. Take 3g of epoxy resin E44 and disperse it in 10g of acetone, then place it in a dropper, wash the residual resin and pour the washing liquid into the dropper. Pass condensed water, turn on the mechanical stirring, heat the reactor temperature to 90°C, open the dropper after the temperature stabilizes, and add the resin to the reactor. The dropping time is controlled at 40min. After the drop addition is completed, clean the dropper and raise the reactor temperature to 110°C. Continue the reaction for 4.5h and then discharge the material to obtain the repair agent component A.

[0053] 100 g of epoxy resin E44, 1.5 g of alkane oil (C12), 199.5 g of ferrosilicon powder (75#), 3.3 g of carbon black (C311), etc. were mixed evenly to obtain repair agent component B.

[0054] Mix repair agent component A and repair agent component B in a ratio of 3.5:1, mature for about 5 minutes, and apply to form a film.

[0055] The samples were then placed in a constant temperature and humidity chamber at 25°C and 50% humidity for 7 days to test their physical and anti-corrosion properties.

[0056] Table 1 sample Adhesion (MPa) Pencil hardness Bending strength (mm) Impact strength (cm) Water resistance (h) Acid resistance (h) Alkali resistance (h) Example 1 5.21 2H 2 50 48 168 168 Example 2 4.85 H 2 50 48 160 168 Example 3 4.52 H 2 50 40 124 168 Example 4 6.70 2H 2 50 48 168 168 Example 5 10.46 3H 2 50 48 168 168 Example 6 4.10 H 2 50 48 168 144 Comparative Example 1 2.84 H 2 50 48 168 100 Comparative Example 2 4.58 2H 2 50 48 168 168

Claims

1. A method for preparing a solvent-free tank bottom repair agent, characterized in that: The following steps are involved: (1) uniformly dispersing the epoxy resin in an organic solvent to obtain an epoxy resin slurry; (2) adding a small molecule amine to a reactor, while introducing nitrogen protection; turning on mechanical stirring, and heating the small molecule amine to a pre-crosslinking reaction temperature; after the temperature stabilizes, slowly dripping the resin slurry obtained in step (1) into the reactor until the color of the reaction solution turns light yellow and the color no longer changes; (3) Raising the temperature of the reactor to the reaction temperature, and continuing to slowly dropwise add the resin slurry obtained in step (1) into the reactor. After the temperature stabilizes, continue the reaction until completion; (4) After the reaction is completed, stop heating, turn off the nitrogen, stop stirring, cool to room temperature, and obtain repair agent component A; (5) Evenly mixing the epoxy resin, lubricant, inorganic filler and optional organic filler to obtain a repair agent component B; Among them, the pre-crosslinking reaction temperature is 80±10 ℃, and the reaction temperature is 100±10 ℃.

2. The preparation method according to claim 1, characterized in that: The organic solvent includes one or more of ethanol, methanol and acetone, preferably acetone.

3. The preparation method according to claim 1, characterized in that: The small molecule amine includes one or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, N-aminopiperazine, polyamide, and dimethylimidazole.

4. The preparation method according to claim 3, characterized in that: The small molecule amines include two or more of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, N-aminopiperazine, polyamide, and dimethylimidazole.

5. The preparation method according to claim 1, characterized in that: During the pre-crosslinking reaction of step (2), the mass ratio of the amount of the resin slurry added in terms of epoxy groups to the active amine of the small molecular amine is 1:10-1:

5.

6. The preparation method according to claim 1, characterized in that: The reaction time in step (3) is 3.5±1 h.

7. The preparation method according to claim 1, characterized in that: In step (3), the total amount of the resin slurry added in terms of epoxy groups to the active amine mass ratio of the small molecule amine is 1:10-8:

10.

8. The preparation method according to claim 1, characterized in that: The lubricant is selected from one or more of alkane oil and dimethyl silicone oil; the inorganic filler includes one or more of ferrosilicon powder, carbon black, calcium carbonate, silicon dioxide and titanium dioxide.

9. The preparation method according to claim 1 or 8, characterized in that: The organic filler is organic bentonite.

10. The solvent-free tank bottom repairing agent obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Epoxy resin base fast repairing material and preparation method thereof

    CN101121812A

  • Epoxy resin material with high tensile strength

    CN102558504A

  • High temperature-resistant step-cured epoxy paint and application method thereof

    CN103319984A